Tindak Tutur Ilokusi pada program Catatan Najwa di YouTube - Putri Ramadhani, Melani; Hermaliza, Hermaliza (UIR Press, 2024)
The phenomenon found in the speech carried out by the host and resource person on the Najwa Note program on Youtube with the theme